Dermoscopic findings in bowenoid papulosis: report of two cases - Carolina Marcucci; Emilia Cohen Sabban; Paula Friedman; Rosario Peralta; Ignacio Calb; Horacio Cabo (Mattioli1885, 2014)
Bowenoid papulosis (BP) corresponds to an in situ squamous cell carcinoma (SCC) located in the anogenital region. It is related to HPV, and presents with gray-brown elevated papules or plaques. A biopsy is needed to confirm the diagnosis; however, dermoscopy may be useful to differentiate this disease from other conditions, such as genital warts, seborrheic keratosis and lichen planus. In this paper we describe the dermoscopic findings in two patients with this disease.